Vaccines efficacy to SARS-CoV-2 variants require holistic knowledge of viral immunology and protein biochemistry - Sachin Kumar (Taylor & Francis Group, 2021)
The article by Abdalla et al., published in the journal on 28 May 2021, raised a concern. The SARS-CoV-2 spike (S) protein is the major targeted surface glycoprotein in COVID-19 vaccines. Many mutations in the S protein of SARS-CoV-2 have been reported across the globe. The S protein plays a crucial role in the induction of neutralizing antibody and protective immunity against SARS-CoV-2 infection. The protein biochemistry and immunology, in addition to conventional virology, will help us to delineate the biology of SARS-CoV-2 variants.